(untitled) (Journal of Educational Sciences, 2025)
Project-research activity in elementary school is an opportunity to become not just a teacher, but also a mentor who opens the way for children to self-discovery and the science universe; it is a unique chance to educate a generation that is not afraid to ask questions and seek answers, forming a society of innovators and thinkers. This study focuses on identifying factors that influence the motivation of young elementary teachers in Kazakhstan with up to three years of experience to engage in project-research activities. A survey followed by semi-structured interviews with 28 participants identified key internal and external factors, which were then analyzed using a SWOT-analysis. Participants rated the importance of the factors on a Likert scale and then the data were processed using descriptive statistics for weighting. The study revealed that teachers see project activities as an opportunity for innovation, self-fulfillment, and professional advancement; however, they reported facing limitations such as time constraints, insufficient teaching and learning resources, and the problem of developing relevant projects. As their advantages as researchers, teachers noted their interest in modern technologies, communication skills, and professional qualities, while their disadvantages included troubling time management, inexperience, fears, and insecurity. For visualization, the findings are presented as a SWOT matrix. The final stage was drawing up recommendations to increase teachers’ motivation. The importance of overcoming barriers for successful project-research performance is emphasized.